Understanding human behaviour in flight operation using eye-tracking technology - Korek, Wojciech Tomasz; Mendez, Arthur P.; Asad, Hafiz Ul; Li, Wen-Chin; Lone, Mudassir (Springer, 2020)
A clear understanding of how the pilot processes the information in the cockpit while carrying out particular tasks is crucial for developing the Human-Machine Interface and inceptors that help reduce pilot workload. Eye-tracking data synchronised with aircraft dynamics data is used here to study the high-workload scenario of executing an offset landing in an engineering flight simulator. The study focused on identifying differences in behavioural patterns between line pilots and test pilots. Evidence for significant differences were found regarding the ability to multitask and monitor aircraft states. The research output will lead to reduction of the pilot’s workload and, in further study, proposition of a new display setups and inceptors.
Keywords: Flight simulation; Eye-tracking; Situation awareness; Human behaviour